Trade Integration as a Pathway to Development? - World Bank (Washington, DC: World Bank, 2019)
After a period of rapid economic growth associated with high commodity prices, the Latin America and Caribbean region has again entered a phase of lackluster performance. Overall this slowdown seems more self-inflicted than imported, and the outlook for the region is not encouraging either. A tepid export response constrains the prospect of growing through external demand whereas limited fiscal space leaves little room to stimulate domestic demand. The outlook could deteriorate further if the international environment became less conducive.